Storja ta' Malta - Pace, Tony (Directorate for Quality and Standards in Education, Curriculum Management and eLearning Department, 2011)
"The author takes a look at everything that happened in Malta at the time when the Maltese Islands were a colony of Great Britain. It is a fairly recent period and many older relatives of our students remember it. This period is part of modern Malta. Here we have a workbook that is not just a narrative or a research, a workbook whose ultimate goal is for students to be able to acquire the skills needed to know what Malta has gone through over the ages." -- Raymond Camilleri, Director of Curriculum and eLearning (Page III, aus dem Maltesischen übersetzt).